2017
DOI: 10.1038/nature22047
|View full text |Cite
|
Sign up to set email alerts
|

Cell diversity and network dynamics in photosensitive human brain organoids

Abstract: In vitro models of the developing brain such as 3D brain organoids offer an unprecedented opportunity to study aspects of human brain development and disease. However, it remains undefined what cells are generated within organoids and to what extent they recapitulate the regional complexity, cellular diversity, and circuit functionality of the brain. Here, we analyzed gene expression in over 80,000 individual cells isolated from 31 human brain organoids. We find that organoids can generate a broad diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
1,180
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,019 publications
(1,223 citation statements)
references
References 44 publications
37
1,180
4
2
Order By: Relevance
“…Building on these earlier works, a recent flurry of papers described the generation of various neural organoids (Table 1), ranging from the whole‐brain organoids,27, 28, 29 to large sub‐brain regions such as cortical organoids,30, 31 to specific regions, including cerebellum,32 midbrain,33 adenohypophysis,34 hypothalamus,35 and hippocampus 36. Comparing with the classical neurospheres, these organoids are generally much larger.…”
Section: Brain Organoids: Current Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on these earlier works, a recent flurry of papers described the generation of various neural organoids (Table 1), ranging from the whole‐brain organoids,27, 28, 29 to large sub‐brain regions such as cortical organoids,30, 31 to specific regions, including cerebellum,32 midbrain,33 adenohypophysis,34 hypothalamus,35 and hippocampus 36. Comparing with the classical neurospheres, these organoids are generally much larger.…”
Section: Brain Organoids: Current Technologiesmentioning
confidence: 99%
“…In addition, even within the same batch of organoids, there is variation among the organoids in terms of the parts of brain represented and their spatial distributions 28. As a result, current methods are most suited to investigate strong or overt phenotypes.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional neuronal activity has been demonstrated with patch clamp recordings of sliced cerebral organoids (5). Additionally, spontaneous neuronal network activity is beginning to be reported in cerebral organoids using high density silicon microelectrodes (6). Further possibilities of high density multielectrode array analysis may allow for additional characterization of cerebral organoid neural networks in both WT and experimental conditions.…”
Section: Commentarymentioning
confidence: 99%
“…Time will tell just how much information these mini-brains can provide. ■ 6 induced PSCs to form a cell layer that self-patterned into organoids composed of multiple brain regions. Measurements of neuronal activity revealed that the organoids contain cells that respond to light in a similar way to photoreceptor cells of the retina, demonstrating that neurons can mature in organoids.…”
mentioning
confidence: 99%